Multiresidue determination of 29 pesticide residues in pepper through a modified QuEChERS method and gas chromatography–mass spectrometry. (11th May 2016) - Liu, Min; Xie, Yan; Li, Haichang; Meng, Xingang; Zhang, Yuping; Hu, Deyu; Zhang, Kankan; Xue, Wei
Abstract: This study describes the development and use of a modified quick, easy, cheap, effective, rugged and safe (QuEChERS) method coupled with gas chromatography with mass spectrometry to determine 29 pesticide residues in green, red and dehydrated red peppers. Pesticides were extracted with acetonitrile (1% acetic acid), partitioned with sodium chloride and purified with primary secondary amino and octadecyl silane in acetone. The QuEChERS extraction conditions were optimized, and the matrix effects that might influence recoveries were evaluated and minimized using matrix‐matched calibration curves. Under the optimized conditions, the calibration curves for 29 pesticides showed good linearity in the concentration range of 0.1–10 μg/mL with determination coefficient R 2 > 0.998. The limits of quantification of the 29 pesticides were 0.006–0.06 mg/kg for green pepper, 0.005–0.039 mg/kg for red pepper and 0.014–0.25 mg/kg for dehydrated red pepper. These values are below the suggested regulatory maximum residue limits. The mean recoveries ranged between 70.1 and 110%, and the relative standard deviations were <13%. The developed method was successfully applied to commercial samples. Some samples were found to contain the 29 pesticides with levels below the legal limits. Copyright © 2016 John Wiley & Sons, Ltd.